2018
DOI: 10.1109/lcomm.2018.2871828
|View full text |Cite
|
Sign up to set email alerts
|

Per-Antenna Power Distribution of a Zero-Forcing Beamformed ULA in Pure LOS MU-MIMO

Abstract: An analytical model is presented to determine the perantenna power distribution of a beamformed M-element uniform linear array (ULA) as a base station antenna (BSA). The analysis assumes a single sector cell serving two user equipments (UEs) in a downlink multiuser multiple-input multiple-output (MU-MIMO) system employing zeroforcing (ZF) transmission. Determinative design parameters of the BSA configuration are identified. Afterwards, their effects on the power spread across the array are investigated when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The grating lobes may cause a high correlation among the channel vectors of users with a large angular separation (not co-located users). To avoid grating lobes, in [11] a maximum allowable δ, depending on the fieldof-view (FOV), is proposed, where the increase in the aperture size is minimal for wide FOVs. Increasing δ is reported beneficial in terms of spectral efficiency for a BS antenna array with a fixed number of antennas [12].…”
Section: Introductionmentioning
confidence: 99%
“…The grating lobes may cause a high correlation among the channel vectors of users with a large angular separation (not co-located users). To avoid grating lobes, in [11] a maximum allowable δ, depending on the fieldof-view (FOV), is proposed, where the increase in the aperture size is minimal for wide FOVs. Increasing δ is reported beneficial in terms of spectral efficiency for a BS antenna array with a fixed number of antennas [12].…”
Section: Introductionmentioning
confidence: 99%
“…Solution: In [26] it is shown that, by employing a ULA equipped with a zero-forcing (ZF) precoder, there exists a maximum allowable d which prevents grating lobes from entering the FOV. For instance, L = 3 results in FOV = 40 • and by using [26, Eq.…”
Section: Proposed Bsa Configurationmentioning
confidence: 99%
“…However, in practice the number of base station antennas is limited and the propagation environment is not necessarily favourable [4], [5]. Spatial correlation among UEs has been observed as a degrading factor, which reduces the downlink sum-rate and increases the dynamic range of the power distribution across the array while linear precoders are applied [6]- [8]. Although in a LoS propagation the correlation depends on the angularseparation between UEs, the richness of scattering is a more critical parameter for the system sum-rate in a NLoS scenario [6].…”
Section: Introductionmentioning
confidence: 99%